The night before Christmas - Moore, Clement Clarke, 1779-1863; Ives, Penny (New York : Putnam, 1988)
In this famous poem, Saint Nicholas visits a sleeping household on Christmas Eve.
Keywords: Santa Claus -- Juvenile poetry; Christmas poetry; Children's poetry, American; Toy and movable books -- Specimens; Santa Claus -- Poetry; Christmas -- Poetry; Narrative poetry; American poetry; Toy and movable books